Dependence of microstructure and magnetic properties of (Nd,Pr)-(Fe,Ti,C)-B melt-spun ribbon on quenching wheel speed - Sabbaghizadeh, Rahim; Hashim, Mansor; Moraddeh, Sasan (The Korean Institute of Metals and Materials & Springer, 2013)
Melt-spun ribbons with nominal composition of Nd6Pr1Fe76B12Ti4C1 have been prepared at different quenching wheel speeds (5, 7.5, 10 and 15 m/s) and investigated for microstructural and magnetic properties. The asspun ribbons were examined by using x-ray diffractometry (XRD) with Cu-kα radiation and differential scanning calorimetry (DSC) and vibrating sample magnetometry (VSM). Based on the results obtained, it was shown that the lower speeds increased the magnetic properties. Hence, a uniform Nd2Fe14B/Fe3B nanocomposite structure with fine soft grains can be developed at an optimum quenching wheel speed of about 5 m/s. Further, it is seen that the higher quenching wheel speed leads to a lower grain size and higher amorphous phase amount.